Pelatihan Dasar-Dasar Public Speaking yang Efektif bagi Komunitas Bank Sampah di Tambun Selatan - sirait, Koramen Haulian; Nico Lucito; Lydia Rosintan; Agustina Suparyati (PT. Cendekia Sapta Indonesia, 2025)
Public speaking is a fundamental skill essential for individuals, especially those who frequently interact with the public. The Waste Bank Community in Tambun Selatan, Bekasi, as the partner of this program, still faces challenges in delivering messages clearly, confidently, and persuasively during socialization and community presentations. To address these needs, the Faculty of Economics and Business, Trisakti University, organized a Community Service program focusing on training the basics of effective public speaking for Waste Bank members. The training methods included counseling, interactive discussions, presentation simulations, and role-play exercises based on real cases encountered by the community. Thirty members participated in the program, selected through recommendations from the Waste Bank administrators. Evaluation was conducted through pre-test and post-test to measure improvements in speaking techniques, audience engagement, body language, and self-confidence. The results showed significant improvement in participants’ public speaking skills, with average scores increasing from 50% in the pre-test to 83% in the post-test. Participants also demonstrated greater confidence in speaking publicly, better structured presentations, and improved vocal and body language techniques. This program proves that practice-based training effectively enhances community members’ public speaking skills. Future training initiatives are expected to be sustained to further strengthen communication capacity in conveying environmental messages to the broader community.